(3TQM JMaI GdehOhO aj GdebUhQ hGdeeOhOs - (3GdeNJGQ GdcfJis; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3GdMeO ddg ai GdcQe hGdLhO MJi JjSQ eG bUOJg ef TQM JMaI GdehOhO LGQjJ eUfag CHG YHO Gddg eMeO Hf eGdc , hWGhdJg ai LejY GdeSGdc aCHQRJ eNOQGJ ZQGFHg hgPHJ eG ajg HGH eG jaJM Chdg s
(3BNQgG (B:s
(3bhdg (B: (3hfjd LhGQge , Ci GdXaQ HLhGQge EeG HGdehJ hjMJed Cfg jQjO HPdc LhGQi EjGge hGdSYOGA LeY SYjO aYjd HeYfi eaYhd ced HMeO dGdg TQM GdTjM GdeNJGQ GdcfJi s
(3HgG fXGe GdJYbjHIs
(3bGd GdfGSN Efg cJHgG ef fSNI cKjQI GdJUMja hGdJMQjas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B130s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs